Model Kemitraan CSR untuk Pengembangan UMKM yang Berkelanjutan: Studi Kasus Program Kemitraan pada PT Jasa Marga (Persero) Tbk: CSR Partnership Model for Sustainable MSMEs Development: A Case Study of the Partnership Program at PT Jasa Marga (Persero) Tbk - Yani Hendrayani; Siti Maryam; Uljanatunnisa Uljanatunnisa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research aims to examine Corporate Social Responsibility (CSR) Partnership Program to find an optimal and sustainable partnership model between State-owned Enterprises (SOEs) and Micro Small and Medium Enterprises (MSMEs) to advance the people's economic sector. This research was qualitative research with a case study approach. Data collection techniques used in this research were in-depth interviews, observation, and literature studies. In-depth interviews were conducted with 3 informants chosen as representatives of PT Jasa Marga (Persero) Tbk and 6 informants were taken as participants in Focus Group Discussions representing MSMEs fostered partners in the Jagorawi - Cikampek Toll network area. Informants were selected using a purposive sampling technique. The results showed that the CSR partnership model between SOEs and MSMEs is based on mutual respect, transparency, good communication and trust, mutual benefit to those involved, and has a consistent commitment from both parties.